HISTORY OF SURGICAL SERVICE IN PRIKAMYE - Palatova, L.F.; Nechaev, O.I. (Perm Federal Research Centre Journal, 2015)
The authors give a short piece of information about the history of surgical service development in Perm Region since first records concerning the appearance of medical institutions in Prikamye up to medical science and practice of today.